(untitled) (Fiep Bulletin - online, 2011)
Deficiencies are defined as congenital absence or hypoplasia of a bone, being sufficient to cause a significant deformity that can be detected at birth or during a physical examination. The two congenital abnormalities of the femur most common are: the proximal focal deficiency (CRD), and no bone defects, called congenital short femur (FCC) or simply hypoplasia of the femur. The congenital short femur is approximately 10% lower than the normal femur. Rarely total inequality of the lower limb is greater than 6cm. If this gap provided between the members is greater than 5cm, can contemplate the lengthening of the femur. According to literature, a form of treatment used in congenital short femur is the bone elongation, in which the techniques employed the use corticotomy and external fixation of the stretch. Case report: patient MAC, 7 year-old male with a clinical diagnosis of congenital short femur left, being carried out by bone of 07cm, through the use of external fixator, linear throughout the period March 2007 to March 2008. The aim of this study is to demonstrate the intervention of physiotherapy in the treatment of congenital short femur after bone distraction by a case report.